Social media influencer marketing: A systematic review, integrative framework and future research agenda - Vrontis, Demetris; Makrides, Anna; Christofi, Michael; Thrassou, Alkis (My University, 2021)
Over the past few years, the popularity of social media influencers (SMIs) has been growing exponentially, making influencer marketing (IM) prevalent in firm strategies. Despite the mounting interest of researchers and practitioners, the resulting scholarly work remains divergent, partial and fragmented. In light of the pivotal role of SMIs on the consumer decision journey and as this research domain is still developing, a comprehensive and critical overview of extant research on this topic is sorely needed. In response, this paper is the first to consolidate the present state of research on IM within social media settings. More specifically, a systematic review of relevant studies published in peer-reviewed academic journals across diverse fields was conducted in order to identify key themes and dominant concepts. The analysis of 68 articles from 29 Chartered Association of Business Schools-ranked journals forges a robust understanding of this phenomenon, shedding light on the mechanisms underlying the appeal of SMIs and their influential power in shaping consumer attitudes and behaviour. Based on the analysis, an integrative multidimensional framework is presented that considers antecedents, mediators and moderators of potential outcomes, as well as contextual factors that translate into consumer behaviour. In so doing, various research gaps are identified and avenues for future research are proposed that reflect important emerging areas and unexplored realms with reference to theory, context and methodology. Conclusively, implications of this study for theory and practice are discussed.
Keywords: consumer behaviour; influencer marketing; social media; social media influencers; social media platform; systematic literature review